Effect of Alnus subcordata, Acer insigne and Sequoia sempervirens plantations on plant diversity in Hyrcanian forest of Iran - FATEMEH GHEIBI; MOSLEM AKBARINIA; YAHYA KOOCH (Society for Indonesian Biodiversity, 2015)
Gheibi F, Akbarinia M, Kooch Y. 2015. Effect of Alnus subcordata, Acer insigne and Sequoia sempervirens plantations on plant diversity in Hyrcanian forest of Iran. Biodiversitas 16: 10-15. Forest plantation is a common action in order to restore thedegraded forests in Hyrcanian forests of Iran. This study compares the plant biodiversity in four 25-year-old stands of plantation,adjacent understorey of alder (Alnus subcordata C. A. Mey.), maple (Acer insigne Boiss.), sequoia or red wood (Sequoia sempervirens(D. Don) Endl.) and mixed stand (maple and sequoia), located in Salmanshahr of Mazandaran Province, northern Iran. Research carriedout in, 10 sample plots with 20m Ã— 20m area which taken by systematic-random in each plantation. All understorey species wereidentified, recorded and then the biodiversity indices (diversity, richness and evenness) were calculated. Our findings show that theplanted species had significant effects on understorey diversity. Statistical comparisons revealed that the highest and lowest diversity(Simpson and Shanon-Winer) and richness (Margalef and Menhinic) indices occurred in sequoia and alder stands, respectively. Theevenness indices (Camargo and Smith-Wilson) were significantly greater in maple, sequoia and mixed stands compared with the aldertype. As a conclusion, floristic change trends were different according to the planted tree species. A good understanding of thecomplexity of vegetation processes requires long-term monitoring of vegetation change.